095 Suicidal ideation among elite athletics athletes: cross-sectional study of associations with sexual and physical abuse victimization and psychological resourcefulness. (3rd March 2020) - Timpka, Toomas; Spreco, Armin; Dahlström, Örjan; Jacobsson, Jenny; Kowalski, Jan; Bargoria, Victor; Mountjoy, Margo; Svedin, Carl Göran
Abstract : Background: Physical and sexual abuse victimization have been connected with negative effects on health long after the abuse has stopped. When athletes encounter situations of defeat and entrapment, the likelihood that suicidal ideation will emerge is increased in situations when negative motivational elements are present, for instance, at low levels of social support. Objective: To examine associations between suicidal ideation and sexual and physical abuse among active and recently retired elite Athletics (track and field) athletes. Design: Cross-sectional study. Setting: Swedish elite Athletics. Participants: Athletes (n=402) who had been selected for a Swedish Athletics team for international competitions between 2011 and 2017. Assessment of risk factors: Lifetime experience of sexual and physical abuse, athlete personal and sociodemographic characteristics, Athletics participation, sense of coherence (SOC-13), and coping strategies (Brief Cope). Main outcome measurements: Suicidal ideation and 1-year period prevalence of non-sports injury. Results: 192 athletes (47.8%) returned complete data sets. The prevalence of suicidal ideation was 15.6% (males 17.4%; females 14.2%) and the non-sports injury prevalence was 8.0% (males 11.6%; females 5.7%). Suicidal ideation was among females (Nagelkerke R 2 =0.33) associated with sexual abuse victimization (Odds ratio (OR) 5.94, 95% Confidence interval (CI) 1.42–24.90; P =0.015) and lower sense of coherence (OR 0.90, CI 0.85–0.96; P =0.001). Among males ( R 2 =0.25), suicidal ideation was only associated with use of behavioural disengagement for coping (OR 1.51, CI 1.18–1.95; P =0.001). Non-sports injury prevalence was among females ( R 2 =0.23) associated with sexual abuse victimization (OR 8.61, CI 0.02–0.90; P =0.039) and participation in an endurance event (OR 7.37, CI 1.11–48.90; P =0.039), while among males ( R 2 =0.11) only having immigrant parents (OR, 5.67, CI 1.31–24.45; P =0.020) was associated with having sustained an injury outside sports. Conclusions: Given that about one out of six athletics athletes had experienced suicidal ideation, the present results warrant and can be used in suicide prevention among elite athletes.